German Society for Emergency Medicine (DGINA) statement on overload situations in emergency departments: Part 1: terminology and legal aspects Stellungnahme der Deutschen Gesellschaft Interdisziplinäre Notfall- und Akutmedizin (DGINA) zu Überlastungssituationen der Notfallabteilungen: Teil 1: Terminologie und rechtliche Aspekte - Hüfner, A.; Dormann, H.; Schäfer, R.; Marohl, R.; Kudlich, Hans Peter Richard; Steenberg, J. G.; Pin, M. (Notfall und Rettungsmedizin, 2024)
Overcrowding and exit block jeopardize patient safety in emergency departments, increase patient mortality, and lead to staff overload. Critical care situations are accompanied by numerous legal uncertainties and open questions regarding liability in the event of harm. The causes of overcrowding and exit block are complex and often not directly influenced by the emergency department itself. Nevertheless, it is essential to maintain the necessary duty of care in such situations. In this context, definitions of terms, legal foundations and risks, as well as methods for objectively documenting overload situations, are presented.
CRIS-Team Scopus Importer:2025-02-03
Keywords: Crowding; Definitions of terms; Exit block; Forced centralized patient allocation; Overcrowding